Politics and Policy Knowledge in Federal Education - Putansu, Steven. author. aut Link
XXIII, 215 p. 17 illus., 13 illus. in color.
Keywords: “In this important book, Putansu argues cogently that a simplistic adherence to ‘evidence-based policy’ has negatively impacted how we understand the interplay of policy knowledge, decisions purposes and politics.” —Jenny M Lewis, Professor of Public Policy, The University of Melbourne, Australia “Putansu offers a compelling assessment of policymakers’ struggle to put policy knowledge to good use, while signposting the factors that make a more realistic marriage of policy knowledge and policy making.” —Donald Moynihan, Professor, McCourt School of Public Policy, Georgetown University, USA “Putansu skillfully unpacks the complexities and politics information production and consumption in the US federal government.” —William Resh, Associate Professor, Sol Price School of Public Policy, University of Southern California, USA Policy knowledge derived from data, information, and evidence is a powerful tool for contributing to policy discussions and debates, and for understanding and improving the effectiveness, efficiency, and equity of government action. For decades, politicians, advocates, reformers, and researchers have simultaneously espoused this value, while also paradoxically lamenting the lack of impact of policy knowledge on decision making, and the failure of related reforms. This text explores this paradox, identifying the reliance on a proverb of using policy knowledge to supplant politics as a primary culprit for these perceived failures. The evidence in this book suggests that any consideration of the role of policy knowledge in decision making must be considered alongside, rather than in place of, considerations of the ideologies, interests, and institutional factors that shape political decisions. This contextually rich approach offers practical insights to understand the role of policy knowledge, and to better leverage it to support good governance decisions. Steven Putansu is a Senior Design Methodologist at the US Government Accountability Office, Professorial Lecturer at American University, USA, and recipient of a 2017 Arthur S. Flemming Award for Federal Management and Leadership.